ASSESSING THE LEVEL OF INFORMATIZATION CONTROL AND SUPERVISORY AUTHORITIES OF THE RUSSIAN FEDERATION AND THE PROSPECTS FOR DEVELOPMENT IN THIS DIRECTION - T. Anopchenko; L. Alekseeva (Вестник университета)
The authors estimate the level of informatization control and supervisory authorities of the Russian Federation, analyze the problems and complexities of the introduction of electronic technologies in the process of governance. Are identified areas introduction of information technologies in the management of the state, considered the problem of informatization of public authorities. The authors provide recommendations for informatization that improve the efficiency of the control and supervision of public authorities.